Idealized climate change simulations with a high‐resolution physical model: HadGEM3‐GC2. (29th May 2016) - Senior, Catherine A.; Andrews, Timothy; Burton, Chantelle; Chadwick, Robin; Copsey, Dan; Graham, Tim; Hyder, Pat; Jackson, Laura; McDonald, Ruth; Ridley, Jeff; Ringer, Mark; Tsushima, Yoko
Abstract: Idealized climate change simulations with a new physical climate model, HadGEM3‐GC2 from The Met Office Hadley Centre are presented and contrasted with the earlier MOHC model, HadGEM2‐ES. The role of atmospheric resolution is also investigated. The Transient Climate Response (TCR) is 1.9 K/2.1 K at N216/N96 and Effective Climate Sensitivity (ECS) is 3.1 K/3.2 K at N216/N96. These are substantially lower than HadGEM2‐ES (TCR: 2.5 K; ECS: 4.6 K) arising from a combination of changes in the size of climate feedbacks. While the change in the net cloud feedback between HadGEM3 and HadGEM2 is relatively small, there is a change in sign of its longwave and a strengthening of its shortwave components. At a global scale, there is little impact of the increase in atmospheric resolution on the future climate change signal and even at a broad regional scale, many features are robust including tropical rainfall changes, however, there are some significant exceptions. For the North Atlantic and western Europe, the tripolar pattern of winter storm changes found in most CMIP5 models is little impacted by resolution but for the most intense storms, there is a larger percentage increase in number at higher resolution than at lower resolution. Arctic sea‐ice sensitivity shows a larger dependence on resolution than on atmospheric physics. Key Points: Results from the latest Met Office Hadley Centre Climate Model Role of atmospheric resolution on measures of climate response is investigated Many features are robust to changes in resolution